Web interactive multimedia technology evolution - Md Ali, Asma; Richardson, Joan (American Society of Mechanical Engineers, 2011)
Web interactive multimedia system, an information and communication system, is introduced and its attributes are outlined. The system consists of several features such as chat, audio, video, polling, whiteboard and desktop sharing and provides students with the opportunity of real time collaboration. When used in a university blended learning environment, it enables immediate feedback betwwen paticipants across physical space.